Transjugular Approach to Closure of Patent Foramen Ovale Under the Guidance of Fluoroscopy and Transthoracic Echocardiography: A Case Report - He, Lu; Xue, Jian-ying; Du, Ya-juan; Xie, Xue-gang; Wang, Xing-ye; Zhang, Yu-shun (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter closure of a patent foramen ovale (PFO) is a therapeutic option in patients with cryptogenic stroke. For patients in whom PFO closure is indicated when a femoral venous approach is not possible, we describe the successful closure of a PFO with atrial septal aneurysm (ASA) using the transjugular approach.